Emerging Technologies in Computational Cognitive Neuroscience (IntechOpen, 2026)
Computational cognitive neuroscience examines the evolving relationship between brain research and artificial intelligence. It provides a comprehensive understanding of how computer models can simulate and explain complex mental processes. This book examines basic cognitive functions, including vision, attention, memory, language, and decision-making, through the lens of biologically inspired neural networks. The book emphasizes the importance of utilizing neuroscience-based models grounded in evidence to bridge the gap between theory and practice. It also discusses current issues, such as the complexity of models and their relationship to biology, while illustrating how the discipline may influence our understanding of both healthy and unhealthy brains. This book is a valuable resource for anyone seeking to learn more about the science of the mind and the future of intelligent systems. It was written for researchers, students, and professionals.